THE CORRELATION BETWEEN SPEAKING ANXIETY AND SPEAKING ACHIEVEMENT - Eksanti Oktavia Putri; Ridha Ilma; Fitri Alya Okta Sukma (IKIP Siliwangi, 2023)
Speaking is one of the most essential skills students must acquire, but they may experience anxiety when communicating in English. If a student is nervous about speaking, it could make it harder for them to do well. Hence, this research examined the correlation and influence of speaking anxiety and speaking achievement among a sample of tenth grade students with 30 students in a state vocational school in Palembang. The participants were selected using cluster random selection. The researchers utilized the Foreign Language Speaking Anxiety Questionnaire (FLSAQ) to assess speaking anxiety levels. Additionally, a speaking assessment was conducted to assess students' proficiency in speaking. The result revealed no statistically significant relationship between speaking anxiety and speaking achievement, as determined by (sig. 2-tailed) > 0.05. The result suggested that H0_1 was accepted and Hα_1 was rejected.